Spatial Variation of the Distribution of the Poor Population in Salah al-Din Governorate for the Year 2020 - Murad Juma AL- Douri, Sura Kherallah; Ibrahim Al-Samarrai, Hussein Alloon (Journal of Tikrit University for Humanities, 2024)
For the purpose of studying the geographical distribution of the phenomenon of poverty in Salah al-Din Governorate, and based on solid geographical rules, it was necessary to start with a correct step, represented by a spatial distribution of this phenomenon, by adopting a spatially corrected map of the study area at the level of districts and sub-districts, and building a database resulting from the collection of official statistics for the subject of the study. After starting the data process represented by extracting the percentage rate, and then excluding the effect of the average and standard deviation through the application of the standard degree technique, the distribution process was carried out to come out with a set of levels that represent spatial patterns, and based on this geographical distribution, the distribution and the extent of its spatial variation can be detected and analyzed according to the administrative units to maintain the level of districts and sub-districts, to give a clear indication of the nature of the phenomenon of poverty and where it is concentrated, and therefore efforts can be directed to it to support the segment of the poor at their various levels.